Akulturasi religi dalam arsitektur vernakular rumah Melayu Pontianak - Muhammad Hidayat; Budi Prayitno; Dwita Hadi Ratmi (ARTEKS : Jurnal Teknik Arsitektur, 2020)
Religious acculturation in vernacular architecture in the Pontianak Malay house Since its founding, Pontianak has been a multicultural society which is, reflected by the embodiment of the acculturation of traditional house architecture found in the neighborhoods where the city was firstly established and still exist until today. The history this city shows, that multicultural has existed for a long time, as the result of cultural integration of certain ethnic groups in the early formation of the Pontianak sultanate. This research is intended to explore further, the religious acculturation that accompanies the embodiment of ethnic acculturation in the vernacular architecture of the Pontianak Malay house. In this city, Malay is an embodiment of inter-ethnic diaspora who share Islamic faith. This research is a qualitative-descriptive research with a case study approach that involve 30 selected samples. The analysis is based on the extent to which the strength of the religious system of each ethnicity involved in the process of acculturation, with reference to the history of the development of da'wah in Pontianak in particular and in West Kalimantan in general. The study uncovered that religious acculturation embodied in Pontianak Malay vernacular architecture represented the form of tolerance between Islamic religious groups of each ethnicity (acculturation-separative) and in the physical element of acculturation to show respects to the authority of the Bugeinese vernacular (integrative-assimilative acculturation). It is hoped that the results of this study will further enrich the main elements of the vernacular architecture of the Pontianak Malay house, and will further illustrate the richness of Pontianak Malay Culture.